A Link between Nominal Devaluation and Real Devaluation in Floating Exchange Regime an Empirical Investigation for Pakistan - MUHAMMAD NISAR KHAN; IHTESHAM KHAN; RABIA INAM KHAN; MUHAMMAD ILYAS (Journal of Business & Tourism, 2021)
The purpose of this paper is to examine the relationship between nominal devaluation and real devaluation with special reference to Pakistan. The data sample cover the monthly nominal effective exchange rate(NEER) and real effective exchange rate(REER) during the floating exchange regime from 2000-2009.To find this relationship, we have employed some sophisticated tests such as augmented dickey fuller (ADF), & Phillipsperron for unit root tests. As the order of integration of variables are different so ARDL Bounds Test is used to find the long run and short run relationship between nominal devaluation and real devaluation in the context of floating exchange regime of Pakistan, The findings of the study indicates that nominal devaluation leads to real devaluation both in the long run as well as in the short run in the case of Pakistan.